2018
DOI: 10.3892/ijmm.2018.3487
|View full text |Cite
|
Sign up to set email alerts
|

microRNA expression profiles of scar and normal tissue from patients with posterior urethral stricture caused by pelvic fracture urethral distraction defects

Abstract: Pelvic fracture urethral distraction defect (PFUDD) seriously affects the quality of life of patients. At present, there are few effective drug treatments available for PFUDD-induced urethral stricture, which is associated with fibrosis and scar formation in urethra lumen. Emerging evidence suggests that microRNAs (miRNAs/miRs) may be involved in the regulation of fibrosis, and analysis of miRNA expression profiles in urethral scar and normal urethra tissues may therefore benefit the discovery of novel treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“… 29 MiR-9-5p, miR-135a-5p, miR-129-5p, and miR-6720-3p may mediate pathways in cancer, and miR-6720 expression is elevated in hepatocellular carcinoma patients treated by alternariol. 30 , 31 MiR-6734 suppresses colon cancer cell growth via increasing p21 levels, therefore, miR-6734 exerts a key regulatory effect on tumor cell proliferation and survival. 32 Thus, these 7 miRNAs might play important roles in PTC and are warrant to be investigated in PTC.…”
Section: Discussionmentioning
confidence: 99%
“… 29 MiR-9-5p, miR-135a-5p, miR-129-5p, and miR-6720-3p may mediate pathways in cancer, and miR-6720 expression is elevated in hepatocellular carcinoma patients treated by alternariol. 30 , 31 MiR-6734 suppresses colon cancer cell growth via increasing p21 levels, therefore, miR-6734 exerts a key regulatory effect on tumor cell proliferation and survival. 32 Thus, these 7 miRNAs might play important roles in PTC and are warrant to be investigated in PTC.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic fracture urethral distraction defects (PFUDD) is a common disease that could severely affects patients' life quality, largely due to excessive fibrosis and associated urethral stricture (Zhang et al, 2018). The current incidence of PFUDD is noted to be variable, usually between 5 and 25% of pelvic fractures, with a frequency of 0.32-5/100,000 for men and 0.46-7.25/100,000 for women (Alwaal et al, 2015;Barratt et al, 2018;Dixon et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Our group recently performed molecular profiling of microRNAs in PFUDD patients and summarized a few candidate genes that may serve regulatory functions in fibrosis (Zhang et al, 2018). We found that miR-29 expression is moderate in normal and pathogenic scar tissues in PFUDD patients, and that expression of hsa-miR-29b-3p and hsa-miR-29c-3p were both slightly downregulated in scar tissues (0.64 vs. 0.69, scar vs. normal) from PFUDD patients (Zhang et al, 2018). Interestingly, let-7i-5p expression appeared to be one of the highest among all the microRNAs, and its expression showed an increase in scar tissue comparing to normal tissue (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Pelvic fracture urethral distraction defects (PFUDD) is a common disease that could severely affects patients' life quality, largely due to excessive fibrosis and associated urethral stricture [1]. Fibrosis is a key factor responsible for pathologic changes related to urethral stricture (in both primary or recurrent diseases) [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Our group recently performed molecular profiling of microRNAs in PFUDD patients and summarized a few candidates that may serve regulatory functions in fibrosis [1]. We found that miR-29 expression is medium in normal and PFUDD patients' scar tissues, and miRNA sequencing data showed that expression of hsa-miR-29b-3p and hsa-miR-29c-3p were both slightly downregulated in scar tissues from PFUDD patients [1] (although the differences are significant, as the fold is 0.64 and 0.69, scar/normal). In addition, we found that let-7i-5p showed very high expression among all the microRNAs sequenced by microRNA sequencing, and its expression showed an increase in scar tissue comparing to normal tissue (although the difference is not significant).…”
Section: Introductionmentioning
confidence: 99%